Efficacy of a Novel Melatonin-Loaded Gelatin Sponge in Palatal Wound Healing - Salma Nabil Hussein; Gehan Sherif Kotry; Amira Salama Eissa; Lamia Ahmed Heikal; Yasmine Youssri Gaweesh (International Dental Journal)
Objectives: The aim of this research was to assess both clinically and histologically the effect of a topically applied melatonin-loaded gelatin sponge on palatal wound healing after graft harvesting. Methods: Twenty-six patients for whom free palatal graft procurement was indicated were divided equally into 2 groups. In the test group, the donor site was covered by a melatonin-loaded gelatin sponge, and in the control group the site was covered by a placebo-loaded gelatin sponge. Wound healing was evaluated on the day of surgery and at 7 and 14 days postsurgery using photo-digital planimetry. Histologic specimens were taken to verify healing type and rate. Pain was assessed via Visual Analogue Scale (VAS) for 7 days from the day of the surgery. Results: At the 7-day interval, photo-digital planimetry showed a significant decrease in the traced raw area (P = .04) in the test group compared with the control group and a significant increase in the mean area of immature epithelia (P = .04). At the 14-day interval, there was no statistically significant difference in any area of interest. Histologically, the application of melatonin was associated with accelerated healing and superior maturation at all follow-up time points. No significant differences were noted in VAS scores between the 2 groups. Conclusions: Melatonin-treated tissue showed marked clinical improvement in the first week postsurgery, indicating an increased rate of healing. Similarly, histologic analysis revealed significant maturation at both time intervals. A melatonin-loaded gelatin sponge is a novel palatal wound dressing that can be used to improve wound healing outcomes and reduce patient morbidity.